Theoretical and experimental sensing of bone healing by microwave approach. Issue 6 (10th June 2022) - Akdoğan, Volkan; Özkaner, Vedat; Alkurt, Fatih Özkan; Karaaslan, Muharrem
Abstract: A medical imaging system is often required to monitor bone growth or bone healing in patients. X‐ray imaging method is one of the most used imaging systems but it affects human health due to the ionizing effect of X‐rays on matter. In this paper, authors investigated the healing period of a bone structure by using electromagnetic antennas. Two different design approaches were examined which are the monopole antenna approach and the horn antenna approach with the frequency bands of 4–10 and 3–18 GHz, respectively. According to simulation results of the first scenario, radius change of a circular bone from 1 to 8 mm causes a transmission reduction from −13.5 dB to −20 dB at 7 GHz. In the second scenario, the thickness of the bone changed from 0.05 to 20 mm and the corresponding transmission value is reduced from −5 to −25 dB at 10 GHz of constant frequency. All these two approaches showed that the bone variation with time changes the transmission characteristics of detector antennas at the operating frequencies. In the last step of this study, an experimental measurement is carried out by using two opposite horn antennas and a planar bone structure in microwave laboratory. The measured results are in a good agreement with the simulated results in the second scenario. This study gives an opportunity to determine bone healing periods in medical applications by microwave techniques.